ISLAMICITY PERFORMANCE INDEX IN SHARIA COMMERCIAL BANKS IN INDONESIA & MALAYSIA - Saputri, Maya Aulia; Lindrianasari; Syaipudin, Usep (JURNAL INFORMASI, PERPAJAKAN, AKUNTANSI, DAN KEUANGAN PUBLIK, 2024)
This study aims to provide empirical evidence on whether the Islamicity Performance Index affects company performance, as proxied by Return on Assets. The novelty of this research lies in proposing Third-Party Funds as an intervening variable between the influence of the Islamicity Performance Index and company performance. The sample for this study includes 8 Islamic commercial banks in Indonesia and 10 Islamic commercial banks in Malaysia, selected using purposive sampling and secondary data collection methods. The analytical  methods used in this study are hypothesis testing and path analysis.The study provides evidence that the Islamicity Performance Index has a positive and significant impact on Return on Assets, indicating that the Islamicity Performance Index is a relevant indicator that can affect the profitability of Islamic commercial banks in Indonesia and Malaysia. Path analysis testing concludes that third-party funds are not significant as an intervening variable between the Islamicity Performance Index and profitability in Islamic commercial banks in Indonesia and Malaysia. Another finding from the study is that firm size has a positive and significant effect on third-party funds, meaning that a larger firm size is associated with improved performance in collecting third-party funds.